'Interdisciplinarity in African Studies - Carvalho, C. (Conference of the African Studies Association of Italy, 2018)
ASAI Roundtable 'Interdisciplinarity in African Studies’, Conference of the African Studies Association of Italy, Bolonha, 4-6 setembro de 2018.